Shear bond characteristics of steel concrete composite deck slab - Preetha Vellaichamy; Senthilkumar Veerasamy; Vasudevan Mangottiri (Građevinar)
Steel-concrete composite slabs with cold-formed, profiled steel deck sheets are popularly used in steel-framed buildings. In these slabs, the deck platform acts as a working platform during construction and also as tensile reinforcement under in-service load conditions. The shear bond capacity of the composite slab is evaluated in this study for two different profile steel deck sheets. Specifically, their composite behaviour is investigated by casting and testing twelve full-scale composite deck slab specimens using the two-point loading system. In addition, based on the shear span length and profile height, the structural performance of the composite deck slab is analysed in terms of load-displacement response, shear bond capacity, ductility index, and load-slip behaviour. The results show that the most common failure of all tested specimens occurs due to the longitudinal shear failure between the concrete and profile deck sheets. As the longitudinal shear is a complex phenomenon, empirical approaches are used to evaluate the shear bond mechanism between the concrete and profile deck. The verification and comparison of experimental test results are performed with conventional and simplified m-k models based on the profile deck depth. The validated results reveal an acceptable level of reliability for prediction of each profile height based on the m and k interaction values.